2019
DOI: 10.2340/00015555-3149
|View full text |Cite
|
Sign up to set email alerts
|

Serum miR-125a-5p and CCL17 Upregulated in Chronic Spontaneous Urticaria and Correlated with Treatment Response

Abstract: Currently, there exist no generally accepted objective biomarkers for chronic spontaneous urticaria. Therefore, the identification of new categories of biomarkers for chronic spontaneous urticaria are urgently needed. To the best of our knowledge, no published information is available regarding serum miRNA as related to chronic spontaneous urticaria. In this study, we provide new and important findings which show that serum expression of miR-125a-5p and CCL17 are significantly upregulated in patients with acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Furthermore, the expression of upregulated or downregulated miRNA was recently investigated in CSU patients and the data were then validated by reverse transcription qPCR. The expression of miR-125a-5p and CCL17 levels were found to be significantly increased in the sera of these patients and significantly decreased in the remission phase of the disease, suggesting a potential use of miR-125a-5p and CCL17 as biomarkers of activity of CSU 108…”
Section: Novel Biomarkersmentioning
confidence: 87%
“…Furthermore, the expression of upregulated or downregulated miRNA was recently investigated in CSU patients and the data were then validated by reverse transcription qPCR. The expression of miR-125a-5p and CCL17 levels were found to be significantly increased in the sera of these patients and significantly decreased in the remission phase of the disease, suggesting a potential use of miR-125a-5p and CCL17 as biomarkers of activity of CSU 108…”
Section: Novel Biomarkersmentioning
confidence: 87%
“…A study on CSU patients' serum via qPCR arrays showed serum miR-125a-5p and CCL17 were significantly increased. Additionally, the serum miR-125a-5p and CCL17 levels of 12 CSU patients in the remission phase were significantly lower than those in the active phase [36]. As the target gene of miR-125a-5p, STAT3 cooperates with CCL17 to participate in the chemokine signaling pathway, thereby activating the inflammatory pathway related to Th2 cells.…”
Section: Cell Adhesion/chemotaxis Pathwaymentioning
confidence: 93%
“…Demographic, clinical and laboratory information of pemphigus patients were retrospectively collected from medical records. Control serum samples were collected from 65 healthy age- and sex-matched Chinese Han ethnic volunteers as described previously ( 25 ). Pemphigus patients with history of thyroid dysfunction or thyroid surgery, or malignancies were excluded.…”
Section: Methodsmentioning
confidence: 99%